ANALISIS PERBANDINGAN FITUR LAYANAN MOBILE BANKING UNTUK NASABAH KELOMPOK BANK BERDASARKAN MODAL INTI (KBMI IV) - Shinta Nuraini (2023)
Mobile banking is today's information technology to make it easier for customers to make transactions. In addition to facilitating mobile banking transactions, it has various features that are owned by every bank that has mobile banking services. Service features are a type of promotion concept application to attract customers' interest in a product. If the service features are good and guaranteed, of course customers will be interested in the product. Writing this final project aims to find out the service features of the two banks' mobile banking and want to compare the features of mobile banking services for customers, the features of mobile banking such as what is contained in mobile banking and then how the service convenience or satisfaction is. The method of writing this final project used is a qualitative method. The results of the questionnaire collected 63 respondents from the age of 17 to over 35 years who filled out the questionnaire on average knowing what features are contained in the mobile banking services used, and for services Convenience provides convenience in making transactions, respondents choose mobile banking which has an attractive appearance and has complete features and on average respondents use a password security feature that makes the transaction easier.